PENGARUH PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SCARLETT WHITENING PADA KONSUMEN KOTA BLITAR - Nurul Farida (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2022)
This study aims to determine the effect of product, price, and promotion on purchasing decisions of Scarlett Whitening in Blitar Regency. Based on the results of the t test, the product shows a Sig value of 0.287 and the t count shows a value of 1.075, it means that the Sig value is greater than the probability value of 0.05 (0.287 > 0.05) and the t count is smaller than the t table (1.075 < 2.00324). The price variable of the t test value shows a Sig value of 0.000 and t count shows a value of 5.376, it means that the Sig value is smaller than the probability value of 0.05 (0.000 < 0.05) and t count is greater than t table (5.376 < 2.00324) and the variable Promotional t test shows a Sig value of 0.000 and t arithmetic shows a value of 4.547, it means that the Sig value is less than the probability value of 0.05 (0.000 < 0.05) and t count is greater than t table 4.547 < 2.00324). The results of the F test show that the calculated f value of 80.362 is greater than the f table of 2.38 and with a significance of 0.000. Because f count > f table and significance level < 0.05, the regression model can be said that Product, Price and Promotion simultaneously or simultaneously affect on purchasing decisions, while the results of the coefficient of determination test (R2) obtained a value of 0.817 or 81 .7% while 18.3% is influenced by other variables.